Arroyos de cabecera: agricultura y calidad de hábitat. La Campiña de Villanueva del Pardillo (Madrid) - Rovira, José Vicente; CAMARERO ESPARZA, Teresa (Observatorio Medioambiental, 2010)
Agriculture is a mayor disturbing factor of aquatic ecosystems, as in the case of headwater streams, which have a considerable influence over the whole hydrographical network. We present a habitat quality assessment of second order streams (1:5000 scale) draining agricultural or recently abandoned fields. We have assessed 10 stream sections in agricultural land and other 10 ones in fields which were abandoned at least 10 years ago, using three different quality indexes: RBP, RQI and the adapted version of QBR to ephemeral water courses. Quality was higher in abandoned fields than in currently laboured. Major agricultural impacts were channel modification and riparian occupation, both enhancing erosion. The 3 indexes have complemented each other. Stream sinuosity lost is a relevant habitat quality parameter that should be considered in future assessments.
Keywords: Riparian zones; Habitat quality; Headwater streams; Land abandonment; Mediterranean ecosystems